2000
DOI: 10.1046/j.1365-2109.2000.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Field emission scanning electron microscopy and transmission electron microscopy studies of the chorion, plasma membrane and syncytial layers of the gastrula-stage embryo of the zebrafish Brachydanio rerio: a consideration of the structural and functional

Abstract: The structure of the chorion and plasma membranes of gastrula‐stage zebrafish Brachydanio rerio embryos were studied using field emission scanning electron microscopy (FE‐SEM) and transmission electron microscopy (TEM). These studies confirm the outer chorion membrane complex to be 1.5–2.5 μm in thickness and to consist of three layers, electron‐dense outer and innermost layers (0.2–0.3 and 1.0–1.6 μm in thickness respectively) separated by an electron‐lucent middle layer (0.3–0.6 μm in thickness). The middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 24 publications
7
108
0
Order By: Relevance
“…Recent research on the epiboly and somite stages, suggests that the major problem for cryopreservation of zebrafish embryos is the difficulty in gaining sufficient cryoprotectant penetration, particularly in the yolk compartment (Rawson et al, 2000). Hagedorn et al (1996Hagedorn et al ( , 1997 showed cryoprotectant penetration in the blastoderm, but hardly any in the yolk, suggesting that the YSL is one of the main permeability barriers to water and cryoprotectants, hindering the chilling of fish embryos.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on the epiboly and somite stages, suggests that the major problem for cryopreservation of zebrafish embryos is the difficulty in gaining sufficient cryoprotectant penetration, particularly in the yolk compartment (Rawson et al, 2000). Hagedorn et al (1996Hagedorn et al ( , 1997 showed cryoprotectant penetration in the blastoderm, but hardly any in the yolk, suggesting that the YSL is one of the main permeability barriers to water and cryoprotectants, hindering the chilling of fish embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Hagedorn et al (1996Hagedorn et al ( , 1997 showed cryoprotectant penetration in the blastoderm, but hardly any in the yolk, suggesting that the YSL is one of the main permeability barriers to water and cryoprotectants, hindering the chilling of fish embryos. Therefore, there is a considerable interest in the study of this syncytial layer, which envelopes the yolk, in order to identify its structural, functional and physiological features (Rawson et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…At the six-somite stage, the volume of the blastoderm increases to about 40%, leaving the yolk occupying 60% of the embryo (Hagedorn et al, 1997c). Between the chorion and the embryo is the perivitelline space filled with liquid with a chemical composition virtually identical to the surrounding medium (Rawson et al, 2000). The complexity of the teleost embryos is further increased by the unbalanced partial density of water in different compartments.…”
Section: Complexity Of Teleost Embryosmentioning
confidence: 99%
“…Already after 1 or 2 days of incubation, some big deposited particles were notable (Figures 4(a) and 4(b)) in the tested QD suspensions with maximal concentration. Coagulation of the particles dropped their chance to get into chorion pores which are 500-700 nm wide according to the field emission scanning electron microscopy data [10].…”
Section: Quantum Dot Toxicity Assessmentmentioning
confidence: 99%